2016
DOI: 10.3390/antiox5030026
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Water-Soluble Gum from Flaxseed Hulls

Abstract: Soluble flaxseed gum (SFG) was extracted from flax (Linum usitatissimum) hulls using hot water, and its functional groups and antioxidant properties were investigated using infrared spectroscopy and different antioxidant assays (2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS), reducing power capacity, and β-carotene bleaching inhibition assay), respectively. The antioxidant capacity of SFG showed interesting DPPH radical-scavenging capacity (IC50 SFG = 2.5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 41 publications
5
23
2
Order By: Relevance
“…The significantly higher reducing power was noticed at a concentration of 30 mg/ml ( A 700nm = 0.83) and lower at control or 0 concentration ( A 700nm = 0.18) and at a concentration of 5.0 mg/ml ( A 700nm = 0.27). Results are in agreement (but higher in reductive capability rate) with Bouaziz et al () who noticed the same increasing trend of reducing power values with increasing concentration in soluble FSG. Furthermore, Zhang et al () observed the correlation of reducing power with increasing concentrations for five algae polysaccharide.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The significantly higher reducing power was noticed at a concentration of 30 mg/ml ( A 700nm = 0.83) and lower at control or 0 concentration ( A 700nm = 0.18) and at a concentration of 5.0 mg/ml ( A 700nm = 0.27). Results are in agreement (but higher in reductive capability rate) with Bouaziz et al () who noticed the same increasing trend of reducing power values with increasing concentration in soluble FSG. Furthermore, Zhang et al () observed the correlation of reducing power with increasing concentrations for five algae polysaccharide.…”
Section: Resultssupporting
confidence: 91%
“…Comparatively, Liang et al (2017) extracted FSG oligosaccharide by the oxidative degradation of H 2 O 2 and found ABTS radical scavenging rate of 91.2% at 25 mg/ml that is higher than the values obtained in the current study. Moreover, Bouaziz et al (2016) isolated soluble FSG from the flaxseed hull having the scavenging ABTS radicals of 75.6% similar in our case but at a higher FSG concentration of 40 mg/ml.…”
Section: Abts Radical Scavengingsupporting
confidence: 73%
See 2 more Smart Citations
“…An antioxidant molecule is able to reduce the stable radical DPPH, having a deep violet color in solution, to the yellow-colored 1,1-diphenyl-2-picrylhydrazyl (DPPH 2 ) [56]. The results showed that ethanol and water extracts of all samples showed moderate radical scavenging activity when compared to standard antioxidants (Figure 2C,F).…”
Section: Resultsmentioning
confidence: 99%